Sex differences in outcomes of acute pancreatitis: Findings from a nationwide analysis. (27th January 2021) - Sharma, Sachit; Weissman, Simcha; Aburayyan, Kanana; Acharya, Ashu; Aziz, Muhammad; Systrom, Hannah K.; Lew, Daniel; Vohra, Ishaan; Feuerstein, Joseph D.; Pandol, Stephen J.
Abstract: Background: Sex is thought to play a significant role in predicting outcomes in numerous diseases. The role sex plays in acute pancreatitis (AP) remains limited. We sought to determine if sex is associated with hospitalization outcomes in this population, using a large national database. Methods: This was a retrospective study of adult patients with AP utilizing the 2016 and 2017 National Inpatient Sample via ICD‐10 codes. The clinical courses of females were compared to that of males. The primary outcome was all‐cause inpatient mortality. Secondary outcomes, including healthcare utilization, were assessed. Statistical analyses were performed using STATA, version 16.1. Results: Of the 553 480 adult patients hospitalized with AP; 25.3% had AP secondary to alcohol (61.4% male, 38.6% female) and 17.44% secondary to gallstones (48.6% male, 51.4% female). Females were significantly older than males (52.81 years vs 50.97 years, P  < .01). Females had a significantly lower likelihood of mortality (aOR: 0.69), shock (aOR: 0.64), sepsis (aOR: 0.70), acute kidney injury (aOR 0.66), intensive care unit admission (aOR 0.53), and pancreatic drainage (aOR 0.61) as compared to males (all with P  < .01). There was no significant difference between females and males with regards to mean length of stay and hospitalization charges and costs. Conclusions: In this large cohort of patients admitted for AP, despite being significantly older, we found that females had significantly improved clinical outcomes, including lower mortality, compared to males. Further prospective studies are needed to accurately understand these differences to guide clinical practice. Abstract : In a large, nationally representative cohort of patients admitted for acute pancreatitis, Sharma and colleagues found that female patients, despite being older, had significantly improved clinical outcomes, including lower mortality, as compared with male patients. Prospective investigation is needed to accurately understand these differences to help guide clinical practice.